2001
DOI: 10.1590/s0100-879x2001000300009
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal permeability in strongyloidiasis

Abstract: The objective of the present study was to assess intestinal permeability in patients with infection caused by Strongyloides stercoralis. Twentysix patients (16 women and 10 men), mean age 45.9, with a diagnosis of strongyloidiasis were evaluated. For comparison, 25 healthy volunteers (18 women and 7 men), mean age 44.9, without digestive disorders or intestinal parasites served as normal controls. Intestinal permeability was measured on the basis of urinary radioactivity levels during the 24 h following oral a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…In this study, the intestinal permeability test was also undertaken in 11 healthy controls, and our results were similar with other Brazilian studies but greater than those in European studies [39,40]. After statistical treatment using the Student-Newman-Keuls test it was observed that urinary lactulose excretion showed different patterns in the three subgroups, and the same occurred with the lactulose/mannitol ratio, confirming that there was no complete normalization in the values of the negative AGA subgroup.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the intestinal permeability test was also undertaken in 11 healthy controls, and our results were similar with other Brazilian studies but greater than those in European studies [39,40]. After statistical treatment using the Student-Newman-Keuls test it was observed that urinary lactulose excretion showed different patterns in the three subgroups, and the same occurred with the lactulose/mannitol ratio, confirming that there was no complete normalization in the values of the negative AGA subgroup.…”
Section: Discussionsupporting
confidence: 89%
“…Relevantly, decreased serum acetate level was also observed in strongyloidiasis in an endemic area 14 . Contradictory findings of acetate level between serum and fecal samples may be due to a variety of other factors related to SCFA production, not only S. stercoralis infection 16,[35][36][37] . In addition, Bacteroidaceae also harbors several mucin-degrading groups and several of the glycosyl hydrolases identified in Supplementary Table S4 degrade dietary components as well as mucin glycans 38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…This pig whipworm induces a less intense and persistent inflammatory response, although Williams et al[ 56 ] verified that T. suis can mature to adult size and reproduce in humans. That is why we see S. stercoralis as a more potentially useful nematode, as it has proven to significantly diminish the intestinal permeability in humans[ 23 ], altering the interleukin profile in a more systemic way[ 42 ]. The prolonged interaction between S. stercoralis and its host induces a greater immunomodulatory action.…”
Section: Discussionmentioning
confidence: 99%
“…When urinary clearance of 51 Cr-EDTA is decreased, this indicates decreased intestinal permeability. Werneck-Silva et al[ 23 ] demonstrated that infection with Strongyloides stercoralis can diminish intestinal permeability compared to healthy volunteers ( P = 0.0001). Intestinal infection with S. stercoralis led to abnormalities in mucus secretion and intestinal motility, as well as possible loss of macromolecules.…”
Section: Introductionmentioning
confidence: 99%